Self-Efficacy and Impostor Syndrome Among Selected Bachelor of Science in Nursing Students of Cavite State University - Main Campus - Quicho, Jervin Dinglasan; Alfonso, Krisha Koleen A.; Añes, Janette T.; Ilem, Nica Angeline R. (Future Science / FSH-PH Publications, 2026)
Nursing is a psychologically and emotionally stressful profession where students have to reconcile the demands of school, clinical practice, and strength. This paper has discussed the connection between self-efficacy and impostor syndrome among students in a Bachelor of Science in Nursing program at Cavite State University – Main Campus and whether there exists a sex difference in the variables. A total of 258 officially enrolled third- and fourth-year students were identified as having participated in the study in Academic Year 2024-2025 using total enumeration and purposive convenience sampling within the study with the descriptive comparative-correlational design. Frequency and percentage distributions, median, standard deviation, Mann-Whitney U test, Spearman rho and Fisher Z test were used as statistical analyses. Findings showed that the impostor feelings were common among both male and female students with average scores of 67.61 and 68.41 respectively which was categorized as frequent impostorism. Nonetheless, the level of self-efficacy in both groups was high with the mean scores of 30.98 and 29.66. There was no notable difference between the sexes in impostor syndrome (t = 0.392, p = 0.696), whereas, there was a notable difference in self-efficacy (U = -2.229, p = 0.026) with males having more confidence. The combination of intense impostor experiences and strong self-efficacy points has complex preparation in nursing education students believe they are competent but cannot learn to have their victory. These results indicate that self-efficacy can serve as an armor but a weak one against self-doubt.